The Strategic Role of the Government in Promoting Sustainable Infrastructure Development - Kalagison, Miryam Diana; Yesyan, Eben Heser; Rumakat, Laila Qadriyani Malikin; Ichwan, Saiful (Universitas Negeri Makassar, 2024)
This study aims to explore the government's efforts in infrastructure development in the Bamus Bama District of Tambrauw Regency and to identify the factors that hinder infrastructure development in the area. The research method used is descriptive, with a qualitative approach. Data analysis techniques and data validity are applied, where both primary and secondary data collected are reviewed to ensure the completeness of the information obtained. The findings indicate that infrastructure development in the Bamus Bama District of Tambrauw Regency has been implemented effectively. The government has carried out planning by involving the local community in the Bamus Bama District and consulting with them on the infrastructure development programs. The infrastructure development initiatives in the district include road access, residential houses, clean water supply, and the installation of generators for the community. However, several challenges were encountered during the process, including a lack of coordination between the district head and the community, difficulties in transportation access, disputes over compensation between landowners and the local government, and delays in reporting, which often hinder the progress of infrastructure development.